Discontinuous Galerkin method coupled with an integral representation for solving the three-dimensional time-harmonic Maxwell equations. (July 2016) - Gmati, Nabil; Lanteri, Stéphane; Mohamed, Anis
Abstract: In this paper, we present a mathematical and numerical studies of the three-dimensional time-harmonic Maxwell equations. The problem is solved by a discontinuous Galerkin DG method coupled with an integral representation. This study was completed by some numerical tests to justify the effectiveness of the proposed approach. The numerical simulation was done by an iterative solver implemented in FORTRAN.